2019
DOI: 10.1038/s41419-019-1363-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diterpenoid compounds that interfere with Fli-1 DNA binding to suppress leukemogenesis

Abstract: The ETS transcription factor Fli-1 controls the expression of genes involved in hematopoiesis including cell proliferation, survival, and differentiation. Dysregulation of Fli-1 induces hematopoietic and solid tumors, rendering it an important target for therapeutic intervention. Through high content screens of a library of chemicals isolated from medicinal plants in China for inhibitors of a Fli-1 transcriptional reporter cells, we hereby report the identification of diterpenoid-like compounds that strongly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Based on this strategy, we hypothesized that C10 might act as an agonist for Fli-1 expression in prostate cancer cells, which was opposite to the role of Fli-1 in other cancers. For example, professor Ben-David's group has found that Fli-1 was a proto-oncogene in leukemia, and inhibiting the expression of Fli-1 could inhibit the proliferation of leukemia cells and induce apoptosis [23]. Therefore, interestingly, we focused on the opposite conclusion and want to investigate the molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this strategy, we hypothesized that C10 might act as an agonist for Fli-1 expression in prostate cancer cells, which was opposite to the role of Fli-1 in other cancers. For example, professor Ben-David's group has found that Fli-1 was a proto-oncogene in leukemia, and inhibiting the expression of Fli-1 could inhibit the proliferation of leukemia cells and induce apoptosis [23]. Therefore, interestingly, we focused on the opposite conclusion and want to investigate the molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…We tested small molecule drugs targeting the ETS-factors ELK3, or ERG and FLI1 in dexamethasone resistant E/R+ REH cells and found reduced cell viability with sub-micromolar concentration. Inhibitors abrogating FLI1, MEF2C, ELK3, or SP4 activation have been previously shown to have efficacy in different cancers [94][95][96][97][98][99]. Moreover, the small molecule ERG/FLI1 inhibitor tested here has entered a phase 1 study in Ewing sarcoma [100].…”
Section: Single Cell Profiling Techniques Have Challenged How We Defimentioning
confidence: 99%
“…Thus, the therapeutic targeting of FLI1 is an attractive strategy. Accordingly, several classes of compounds with a potent anti-FLI1 activity have recently been identified (18)(19)(20)(21)(22). Among these, two flavagline-like compounds exhibiting potent FLI1 inhibition were also identified (22).…”
Section: Fli1 Promotes Protein Translation Via the Transcriptional Rementioning
confidence: 99%
“…To clone the MKNK1 promoter, various regions of the MKNK1 promoter (for details please see Fig. 2B) were isolated by qPCR (the list of primers is presented in Table SI) and cloned into the luciferase reporter vector PGL3 (Promega), as previously described (21). These promoter vectors (1 µg) with either MigR1 (1 µg) or MigR1-FLI1 (1 µg) were transfected into 293T cells (ATCC-CRL-3216) using Lipofectamine 2000 (Life Technologies; Thermo Fisher Scientific) following the manufacturer's protocol.…”
Section: Cell Lines and Drug Treatment Mycoplasma Negative Erythrolementioning
confidence: 99%
See 1 more Smart Citation